Analisis Normatif Risiko Komodifikasi Pidana dalam Implementasi Restorative Justice pada Kejahatan Harta Benda : A Normative Analysis of the Risk of Criminal Commodification in the Implementation of Restorative Justice in Property Crime Cases - M. Mulabbil Bait; Teguh Karya Pamungkas (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
The implementation of restorative justice in property crimes in Indonesia currently faces significant challenges, particularly the devaluation of “forgiveness,” which has increasingly shifted toward becoming an economic commodity. The practice of “commercializing forgiveness” has emerged as a legal paradox, where restitution mechanisms are often reduced to mere financial transactions aimed at dismissing criminal charges, without addressing the perpetrator's essential moral remorse. Utilizing a juridical-normative research method, this study aims to analyze the risk of legal norm devaluation and the threat to the principle of equality before the law when a perpetrator's economic capacity becomes the primary determinant in the success of penal mediation. The analysis indicates that without rigid regulatory standardization, this mechanism has the potential to create disparities in justice, weaken the deterrent effect, and erode the integrity of criminal law as a means of protecting the broader public interest. Consequently, a reorientation of criminal policy is imperative to ensure that the recovery of material losses does not negate criminal liability, thereby preventing the law from transforming into a negotiable monetary instrument. Implmentasi keadilan restoratif pada tindak pidana harta benda di Indonesia saat ini menghadapi tantangan serius berupa devaluasi nilai pengampunan yang bergeser menjadi komoditas ekonomi. Praktik